Using Historic GLO Data and GIS to Assess the Potential for Local Bison Bison Near Two Wisconsin Late Prehistoric Oneota Localities - (:unkn) unknown (My University, 2019)
Bison (Bison bison) remains are rare in the archaeological record of Wisconsin. This thesis uses a Geographic Information System (GIS) to better understand native vegetation near sites with reported bison bone to assess their ecological viability to support local bison herds. The distribution of bison bone recovered in archaeological contexts in Wisconsin can be summarized as follows: few sites report bison remains, the archaeological contexts that do report bison are clustered in a few Late Prehistoric period locations (approximately A.D. 1300-1650), and bison remains are rare in comparison to other fauna at those sites (Arzigian et al. 1989; Boszhardt 1989, 2000; Boszhardt and McCarthy 1999; Brown and Sasso 2001; Dirst 1985; Gibbon 1970; Jeske et al. 2017; Kreisa 1986; McQuin 2010; Peske 1966, 1971; Sasso 1993, 2014; Scott 1994; Shay 1978; Stevenson 1994; Stoltman 1973; Theler 1994b, 2000; Theler and Boszhardt 2003, 2006; Theler and Pfaffenroth 2010). Sasso (1993, 2014) summarizes three major hypotheses about how bison were acquired by Wisconsin’s prehistoric and historic native residents: local hunting, non-local hunting, or trade acquisition. One comparative approach to assessing the viability of a local hunting hypothesis versus other hypotheses is to consider the vegetative needs of a bison herd, and to model local vegetation around the sites where bison bones have been recovered. This thesis attempts that by considering historic accounts of vegetation, bison biological needs, and GIS modeling.
Keywords: Bison; GIS; GLO; Historic Ecology; Oneota; Wisconsin